The Chobanids of Kastamonu Politics, Patronage and Religion in Thirteenth-Century Anatolia - De Nicola, Bruno (Routledge Studies in the History of Iran and Turkey, 2024)
This book provides a novel approach to the history of medieval Anatolia by analysing political, religious and cultural developments in the region of Kastamonu during the reign of the Chobanid dynasty (c. 1211-1309). During the 13th century, the Chobanids consolidated a local dynasty in western Anatolia - a borderland between Islam and Christianity - becoming cultural actors patronising the production of religious, scientific and administrative works in the Persian language. These works, though surviving today in manuscript form, have received little attention in modern historiography. The book therefore attends to this gap in the research, incorporating a detailed study of texts by little-known authors from the time. The book explores the relationship between Islam and the Chobanid dynasty in the context of the wider process of Islamisation in medieval Anatolia, hypothesising that Turkmen dynasties played a fundamental role in this process of Islamisation and acculturation. The Chobanids of Kastamonu, then, offers an in-depth study of a Turkmen local dynasty that achieved political autonomy, financial independence and cultural patronage in medieval Anatolia vis-à-vis the main political powers of the time. Attentive to religious diversity, state formation and processes of transculturation in medieval Anatolia, the book is key reading for scholars of Middle Eastern history and Islamic studies.